The Outlook and Assessment of Biomedical Research among the Medical and Dental Students - A Cross Sectional Study in Odisha, Eastern India - Ruchi Bhuyan; Sanat Kumar Bhuyan; Shruti Lekha K; Dattatreya Kar; Ananya Kuanar; Gangadhar Sahoo (Medsci Publications, 2021)
Objective: This study was conducted to overview the determination of medical and dental students towards the academic curriculum, research interest and career outlook. From the previous studies the survey questions are collected basing on the medical and dental student's attitudes toward research and their interest towards course curriculum. Methodology: In a Google Form version, the questions were developed and modified to complete the study. For statistical analysis Social Science (SPSS) program, Statical Package version 16 was used for data analysis. Mean± standard deviation was used to report numerical variables. Result: It was found that 37.9 percent would do research to improve their clinical knowledge, 25.5 percent were really interested to carry out research, 20.6 percent would do research with a motive to provide better health care facilities, 7.6 percent to improve their resume, 4.1 percent to get recognition, 4.1 percent to learn new things where as four individuals were not at all interested to do the research. Conclusion: Medical and Dental colleges should include subjects like research methodology in their course curriculum and should provide research infrastructures as well as skilled supervisors in order to motivate and encourage the students for active participation in research.